Reaproveitamento de finos de pedreiras em pavimentação: uma abordagem técnica e econômica - SILVEIRA, Leonardo Ramos da (2010)
The wastes generated by the quarry companies from civil construction represent an activity that has been outstanding because of the countless problems that appear with their stockpiling and maintenance. The great concern with those wastes is linked to the capacity to generate social and environmental effects that can harm the ambient through the appearance of environmental impacts. In this context, researches have been done to study the application of those wastes in paving works, with the propose to reduce the generated problems and to contribute for the appearance of materials that can substitute those that are considered traditional and that are more and more scarce. The objective of this research was to verify the technical and economical viability of the use of quarry wastes in paving, besides complementing the researches previously done with those wastes. For this research the same mixtures used in the experimental pavement were analyzed at laboratory: Mixture 1 (30% filler + 70% soil), Mixture 2 (20% filler + 80% soil), Mixture 3 (20% micaxist powder + 80% soil) and Mixture 4 (30% micaxist powder + 70% soil). In the complementally evaluation, tests of chemical characterization (soil and mixtures), X-ray diffraction and electronic microscopy of sweeping were done. For technical investigation, the experimental pavement evaluation was done in two different periods using load bearing plate test, dynamic cone penetration and Benkelman beam. The economical viability analysis was done by the costs estimated for the execution of each experimental sub-section, simulating different sceneries. The results of the chemical characterization demonstrated that there is an increment of parameters as pH and cation exchange capacity with the incorporation of fine quarries to the soil. The results of X-ray diffraction showed that new minerals are not formed in the mixtures. The results of microscopy of sweeping pointed that the factors that more influences in the mixtures structures are their grain size materials and the compaction energy applied. In the experimental pavement evaluation it was possible to verify the influence of the rain in the pavement structural performance, what provoked high displacements values for the right board. Even so, the sub-sections executed with filler and micaxist powder have been presenting behavior varying among regular and good. In the costs estimated results, it was observed that the sub-sections executed with fine quarry wastes can be considered the most economical, mainly when the minimum distance of competition is considered. Being like this, one can be noted that the reusing of fine quarry wastes in pavements has viability and it contributes significantly for the reduction of environmental effects generated by the mineral sector.